CONDUCTING ENGLISH TEACHING BY USING DIFFERENTIATION INSTRUCTION IN 21ST CENTURY: A STUDENT-CENTERED APPROACH - Daulay, Rizka Fahrina (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2023)
In one class, there are various students with different characteristics and  learning styles. To achieve the learning objectives, the teacher should apply differentiation instruction. In this study, the concept of differentiation instruction is implemented in learning English, a student-oriented approach. The data sources take from learning outcomes conducted in XII MIPA 1 at SMA Negeri 5 Medan in their process of doing the project. The material taught by the teacher in proving this concept is Conditional Sentence Type 2. The learning method used is project based learning. The learning process carried out for this research lasted for four meetings. This research wants to prove that implementing the concept of differentiation instruction can make the students think ingenious while working with groups to produce the original product. In another words, this research aims to prove the teacher's way of conducting the learning process by implementing the concept of differentiating instruction to produce creative and original products. This concept needs to be implemented so the students can apply ConditionalÂ  Sentence Type 2 into their daily lives. The result shows each group could work together as a team to produce poetries and songs by using Conditional Sentence Type 2. Each group was enthusiastic to perform their best work in front of the class. Also, the learning process became purposeful and meaningful.